Adolescent resilience to addiction: a social plasticity hypothesis. (January 2018) - Cousijn, Janna; Luijten, Maartje; Feldstein Ewing, Sarah W
Summary: The prevalence of substance use disorders is highest during adolescence; however, many adolescents experience a natural resolution of their substance use by early adulthood, without any formal intervention. Something appears to be unique and adaptive about the adolescent brain. In this Review, we examine the roles of the social environment and neurocognitive development in adolescents' natural resilience to substance use disorders. At present, little is known about the neurocognitive mechanisms that underlie this adaptive phenomenon, since neurodevelopmental studies have mainly focused on the risk side of the substance use equation: escalation of substance use. To provide a framework for future studies, we put forth a social plasticity model that includes developmentally limited enhanced social attunement (ie, the need to harmonise with the social environment), affective processing, and brain plasticity, which underlie adolescents' capacity to learn from and adapt to their constantly evolving social environments.